Histopathology test workflow modeling in bounds of laboratory information systems - Smoktii, O. D.; Smoktii, K. V.; Kabak, L. V. (Systems and Technologies, 2020)
Laboratory information system (LIS) as a part of information delivery system is a main element in electronic clinical data circulation and medical record storing. The purpose of this article is to build a model of pathology testing workflow in a case of histopathology testing. Created in this paper model could be used in LIS development process. Further development of this model could be integration with the optimization methods to optimize using expensive environments and reagents in laboratories. A state machine is applied to the built model according to the Turing machine, which goes through possible states of the system in which it can be dring histopathological testing process.